Study The Effect Of Karpura Yoga In The Management Of Mootraghata W.S.R. To Bph - Kadam, Rahul; Magar, Vishal; Hansaliya, Nil; N. Bobde, Shraddha (Journal of Neonatal Surgery, 2025)
Mootraghata is an Ayurvedic term that refers to a condition marked by difficulties in urination, often manifesting as urinary obstruction or retention. This condition is particularly prevalent in older males due to anatomical and physiological changes associated with aging, such as Benign Prostatic Hyperplasia (BPH). BPH leads to an enlargement of the prostate gland, which can compress the urethra and hinder normal urine flow. Patients may experience a range of symptoms, including weak urinary stream, frequent urges to urinate, and a sensation of incomplete bladder emptying. These symptoms can significantly affect the quality of life, leading to discomfort and anxiety. Karpura Yoga is a traditional Ayurvedic formulation that has garnered attention for its potential therapeutic effects on urinary disorders. The formulation typically includes camphor (Karpura) as a primary ingredient, along with other herbal components known for their diuretic, anti-inflammatory, and analgesic properties. Clinical observations and preliminary studies suggest that Karpura Yoga can improve urinary symptoms and overall quality of life for patients suffering from Mootraghata linked to BPH. The integration of Karpura Yoga into the management of Mootraghata offers a promising avenue for holistic treatment, aligning with the principles of Ayurvedic medicine. As interest in alternative therapies grows, further exploration into the clinical effectiveness of Karpura Yoga could enhance the standard of care for patients with BPH-related urinary issues.